Surgical Robotics Unveiled: The Robotic Surgeon's Role in Modern Surgical Evolution - Baddam, Parikshith Reddy (ABC Journal of Advanced Research, 2019)
This article delves into the transformative impact of surgical robotics on modern medical practices, unveiling the pivotal role of robotic surgeons in the ongoing evolution of surgery. Through a comprehensive exploration of cutting-edge technologies, the paper investigates how robotic systems enhance precision, minimize invasiveness, and contribute to improved patient outcomes. By scrutinizing recent advancements in robotic-assisted procedures, the article sheds light on the integration of artificial intelligence, machine learning, and advanced imaging technologies in surgical workflows. Emphasizing the collaborative nature of human-robot teams, the discussion highlights the synergy between skilled surgeons and robotic counterparts, emphasizing the potential for enhanced surgical capabilities. Furthermore, the article addresses challenges and ethical considerations associated with the widespread adoption of robotic surgery. In essence, this exploration offers a nuanced understanding of how surgical robotics is shaping the landscape of modern healthcare, offering a glimpse into the future trajectory of this rapidly evolving field.